Vigilancia de la calidad del agua para consumo humano en zonas rurales de la provincia de Moyobamba-2012 - Mendoza Aguilar, Humberto (2013)
The present work entitled "QUALITY WATER MONITORING FOR HUMAN CONSUMPTION IN RURAL AREAS OF THE MOYOBAMBA PROVINCE -2012 ", was developed in the scope of the Moyobamba province, having as aim Evaluate the systems of supply of drinkable water in the rural area of Moyobamba province. The research type is descriptive, was taken as a sample the major population centers in the district of the province, of which has been assessed both the management and service coverage as well as the sanitary status of the water infrastructure for human consumption. It has been possible to identify those responsible for the management of water services in the evaluated localities, as well as the age, procurement system type, the sources and the type of deposits in each case. Likewise it can be concluded that in general the systems water management supply in the rural areas of the Moyobamba province, is inefficient since the responsibility in the conduction of this service is not uniform being different levels of responsibility as are the JASS, the Municipality and by means of communal directive. Also, due to the little income by contributions from users, do not have trained operators and the coverage is not the 100% of the population. In regard to the health status of the water supply infrastructure, it has been found that in most cases, the system has a antiquity considered and do not have alternative systems of abstraction. As well as the sources come from groundwater without treatment. As for the capture, these do not have protective fences and the structures are in bad state of conservation.